CHRONIC HEART DEFICIENT IGI AND CHRONIC KIDNEY DEFICIENCY WITH SICK IN PATIENTS EXTRACORPOREAL OF DETOXIFICATION EFFECT - Pulatova Sh. Kh.; Adizov Kh. P. (Web of Journals Publishing, 2024)
This year Bukhara branch of the Republican Scientific Center for Emergency Medical Care resuscitation in sections a total of 312 people chronic heart deficiency and one transient chronic kidney deficiency with sick Hemodialysis practice in 42 patients take will go of these patients in about 10 percent complication cases with UNE complication and USV hardware with cure measures take to go demand is enough
Keywords: Extracorporeal _ detoxification , hemodialysis, acute breath deficiency.